Small Scale Home Drying of Indigenous Fish Species in Urban High-Rises at Dhaka Metro (Bangladesh Journal of Zoology, 2021)
Drying is one of the common and ancient methods of fish preservation and is generally done in a wide range of open space. This study attempt to evaluate fish drying method at high-rise urban households with three small indigenous fishes namely Mola (Amblypharyngodon mola), Chapila (Gudusia chapra) and Lal Khailsha (Trichogaster lalius). Fishes were dried at high-rise indoor veranda and outdoor rooftop conditions. The dry weight of Mola, Chapila and Lal Khailsha fishes were 70%, 69.5% and 72% in indoor condition and 71.1%, 70.5% and 73% in outdoor condition. The differences of drying capacity between the indoor and outdoor dried fishes were none (p